2016
DOI: 10.5812/hepatmon.56087
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-Reactive Protein in Children with Liver Disease and Ascites

Abstract: Background: The diagnosis of peritonitis as a complication of cirrhosis is an important clinical problem. Objectives: The aim of this study was to evaluate serum C-reactive protein levels as a diagnostic factor for spontaneous bacterial peritonitis (SBP) in child patients with liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Elevated ANC raises probability of infected ascites 9 times more. This was contradictory to other reports done by Preto-Zamperlini et al (2014) and Kalvandi et al (2016) [ 8 , 28 ]. Discrepancy between the results of TLC and ANC as markers of ascitic infection, in our study, could be explained by the fact that patients with CLD usually have splenomegaly and hypersplenism that can mask the TLC elevation in peripheral blood.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Elevated ANC raises probability of infected ascites 9 times more. This was contradictory to other reports done by Preto-Zamperlini et al (2014) and Kalvandi et al (2016) [ 8 , 28 ]. Discrepancy between the results of TLC and ANC as markers of ascitic infection, in our study, could be explained by the fact that patients with CLD usually have splenomegaly and hypersplenism that can mask the TLC elevation in peripheral blood.…”
Section: Discussioncontrasting
confidence: 76%
“…In our study, TLC in the peripheral blood per se showed no statistically significant difference between infected and non-infected ascites patients. Although, other studies found that TLC was significantly higher in patients with AFI [ 8 , 28 ]. We also analyzed ANC as a predictor of AFI and we found that it is a significant independent factor associated with ascitic infection.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Children and adolescents have a number of physiological, psychological, and social needs, one of which is their health (1)(2)(3). However, their health may be affected by diseases such as cancer (4), cardiovascular disease (5), thalassemia (6,7), liver disease (8), rickets (8), and orthopedic diseases (9). They may also be exposed to various diseases that threaten their lives, like other age groups (6,7,9).…”
Section: Contextmentioning
confidence: 99%